Answer:
26.25 questions
Step-by-step explanation:
75% of 35 is 26.25
Answer
g(x) = x^3 − x^2 − 4x + 4
End behavior- Falls to the left rises to the right
y intercept-(0, 4)
Zeros- (1,-2,2)
g(x) = x^3 + 2x^2 − 9x − 18
End behavior- Falls to the left rises on the right
y intercept- (0,-18)
Zeros- (-2,-3,3)
g(x) = x^3 − 3x^2 − 4x + 12
End behavior-Falls to the left rises to the right
y intercept-(0,12)
Zeros- (3,-2,2)
g(x) = x^3 + 2x^2 − 25x − 50
End behavior- falls to the left rises to the right
y intercept(0,-50)
Zeros- (-2,-5,5)
g(x) = 2x^3 + 14x^2 − 2x − 14
End behavior- falls to the left rises to the right
y intercept-(0,-14)
Zeros- (-7,-1,1)
Step-by-step explanation:
~Plz tap the crown~
~ Thank you~
<u>Solution</u><u>:</u><u>-</u>
Let's find roots of x² - 3x + 2
=> x² - 3x + 2 = 0.
=> x² - x - 2x + 2 = 0.
=> x ( x - 1 ) -2 ( x - 1) = 0.
=> ( x - 1 ) ( x - 2 ) = 0.
=> x = 2, 1.
Now
- ( a + ß )² = (2+1)²=3²=9
- ( a - ß )² = ( 2 - 1 )² = 1² = 1.
So , equⁿ would be ,
=> x² - ( 9 + 1)x + 9×1=0.
<u>=> x² - 10x + 9=0.</u>